(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
The development of a foreign language is always associated with the selection of relevant methods. The experience of teaching English by experts of this language is predominant. Its effective implementation and use in training programs, including federal ones, is one of the key issues of teaching English today